Theory of mind and problem behavior in people with intellectual disability - Marija; Đorđević, Mirjana (Specijalna edukacija i rehabilitacija, 2021)
Introduction. Behavioral problems are more common in people with intellectual disability than in typical population and present an obstacle to their adaptive functioning and social inclusion. Since adjusted social behavior requires, among other things, an adequate understanding and interpretation of thoughts and behavior of others, theory of mind could be one of the factors of adjusted behavior and behavioral problems in people with intellectual disability. Objective. The aim of this paper is to single out the research in which the issue of the relationship between the ability of theory of mind and behavioral problems of people with intellectual disabilities has been addressed, through a literature review. Methods. Insight into the available literature was performed by searching the electronic databases that are available through the services of the Serbian Library Consortium for Coordinated Acquisition – KOBSON, as well as through Google Scholar and Research Gate. Results. Based on the analyzed research results, it can be concluded that there is a negative correlation between theory of mind and behavioral problems, both in children and in adolescents and adults with intellectual disabilities. While some studies have found a direct link between theory of mind and behavioral problems, others have found that this link is indirect, whereby the role of intermediaries tend to have executive functions, social acceptance, quality of parental interaction and resilience. Conclusion. Since the results of several studies suggest that more advanced theory of mind enables more successful social interactions and more adjusted behavior, it is necessary to enrich the education of people with intellectual disability with contents related to understanding thoughts, emotions, desires and intentions, as one of the elements of approach to treatment, in order to prevent problematic behaviors.